Evaluasi Program Pendidikan Inklusi dalam Meningkatkan Mutu Pendidikan (LPPM Universitas Buana Perjungan Karawang, 2024)
The aim of this research is to obtain an overview and analysis of the evaluation of inclusive education programs in improving the quality of education based on aspects of planning, organizing, implementing, evaluating, obstacles and solutions in inclusive education in improving the quality of education. This research approach is qualitative research with descriptive study methods. The data collection techniques used were observation, interviews and documentation. Data were analyzed using data reduction, data presentation, and drawing conclusions. The results of this research show that planning for inclusive education in schools has been outlined in the general RPP which is then modified/adjusted to the abilities of each crew member. In organizing inclusive education, the leadership directly assigns an inclusion coordinator. In organizing the school, it only includes the school curriculum section/assisted by GPK to determine what kind of learning curriculum must be carried out. The implementation of inclusive education is implemented in the preparation of RPPs for inclusive schools which look at students with special needs, especially those in each class, and what types of obstacles, so RPPs are prepared in the form of adjustments to the learning outcomes of the students themselves.